Producción del cultivo de rábano (raphanus sativus l.) con diferentes dosis de biostimulantes en el cantón La Maná. - Lobato Magallanes, Genesis Elizabeth (2023)
The present work was developed in the "La Maná" Canton, Cotopaxi Province, where the response of the radish crop (Raphanus sativus L.) was evaluated with different doses of biostimulants, based on gibberellins, cytokinins and humic acids, in dose 0.5ml/L, 1.0ml/L and 1.5ml/L. For this, a completely randomized block design (DCBA) was used with a factorial arrangement of 3x3+1, with four repetitions and 10 treatments including the control, in addition, a nutritional analysis of the best treatment based on performance and a sensory analysis were carried out. qualitative analysis of the radish obtained with 80 non-specialized tasters, the interactions of the morphological variables at 45 days were obtained that the cytokinin and gibberellin treatment is greater with 19,24 and 19,29 respectively and the 1.5ml dose with 20,87 cm, repeating the same tendency in number of leaves with 6,88 and 6,78 units and in dose 7,17, In the development variables taken only at 45 days, humic acid with a dose of 1.5ml is the one that has the best results with a tuber width of 4.52, a tuber weight of 48.13g and a yield of 32,000 Kg/ha, so This was taken as the best treatment and the nutritional analysis was carried out to obtain a product low in carbohydrate, energy, fat and rich in ash, fiber, moisture and protein (higher in 1%; 0,08%; 1,54% and 0 73%), which was compared with the control that was the opposite rich in carbohydrates, energy and fat, the results of the qualitative sensory analysis with a 5-point hedonic scale were obtained, the best results were for the treatment with gibberellin with 1,5 ml dose with criteria between I like it and I really like it, these parameters being important for the acceptance of the product at the consumer level.